2016
DOI: 10.1111/asj.12384
|View full text |Cite
|
Sign up to set email alerts
|

Identification of internal control genes in milk‐derived mammary epithelial cells during lactation cycle of Indian zebu cow

Abstract: The present study aims to evaluate the suitability of 10 candidate genes, namely GAPDH, ACTB, RPS15A, RPL4, RPS9, RPS23, HMBS, HPRT1, EEF1A1 and UBI as internal control genes (ICG) to normalize the transcriptional data of mammary epithelial cells (MEC) in Indian cows. A total of 52 MEC samples were isolated from milk of Sahiwal cows (major indigenous dairy breed of India) across different stages of lactation: Early (5-15 days), Peak (30-60 days), Mid (100-140 days) and Late (> 240 days). Three different statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…In recent past, our groups has conducted number of similar Reference genes for qPCR studies across tissues of riverine buffaloes Reference genes for qPCR studies across tissues of riverine buffaloes studies to identify appropriate reference gene panels for application in transcriptional studies in Indian native cattle and riverine buffaloes. In one such study, β2M, RPS9 and RPS15a genes were identified as best RGs for heat stressed mononuclear cells of Indian cattle and buffaloes [19]; β2M, RPS23, RPL4 and EEF1A1 as most reliable RGs in heat stressed mammary explants and mammary epithelial cells of buffaloes [6,7]; RPL4, EEF1A1, ACTB and GAPDH genes were found to be most stable genes in milk derived mammary epithelial cells in Sahiwal cows during different lactation stages [30]. Similarly identification of stable reference genes for transcriptional studies in bulls distinctive in meat quality [5] and in buffalo muscle tissue [31] were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent past, our groups has conducted number of similar Reference genes for qPCR studies across tissues of riverine buffaloes Reference genes for qPCR studies across tissues of riverine buffaloes studies to identify appropriate reference gene panels for application in transcriptional studies in Indian native cattle and riverine buffaloes. In one such study, β2M, RPS9 and RPS15a genes were identified as best RGs for heat stressed mononuclear cells of Indian cattle and buffaloes [19]; β2M, RPS23, RPL4 and EEF1A1 as most reliable RGs in heat stressed mammary explants and mammary epithelial cells of buffaloes [6,7]; RPL4, EEF1A1, ACTB and GAPDH genes were found to be most stable genes in milk derived mammary epithelial cells in Sahiwal cows during different lactation stages [30]. Similarly identification of stable reference genes for transcriptional studies in bulls distinctive in meat quality [5] and in buffalo muscle tissue [31] were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…A dissociation protocol with an incremental temperature of 95 • C for 60 s, 55 • C for 30 s and 95 • C for 30 s was used to investigate the specificity of qPCR reaction and the presence of primer dimers. Further expression data were normalized with three internal control genes: U6 snRNA, S18, and β5s-RNA and compared using first derivative method [14].…”
Section: Mrna and Microrna Expression Analysismentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) is one of the most powerful and reliable techniques to quantify gene expression. This technique is widely used due to its sensitivity, accuracy and reproducibility in gene expression analysis (Artico et al 2010;Jatav et al 2016). Quantification assays are performed to detect differential expression of a gene(s) involved in plant growth, development, signal transduction and metabolism.…”
Section: Introductionmentioning
confidence: 99%